JALUR REMPAH BANDA, ANTARA PERDAGANGAN, PENAKLUKAN DAN PERCAMPURAN: DINAMIKA MASYARAKAT BANDA NEIRA DILIHAT DARI SOSIO-HISTORIS EKONOMI REMPAH - jalu yogiswara lintang (Jurnal Masyarakat dan Budaya, 2021)
Banda Neira is one of the islands in Central Maluku. A small area far from the district and provincial capitals. Banda Neira has abundant natural resources. At least in this small area, it is now famous for two natural resources which are the main commodities of the community. The first is its maritime potential, so that this area is made by the government to become one of the national fish barns. No wonder the Banda Sea holds a lot of fishery potential, especially tuna, skipjack, momar, grouper and many other types. The second potential is the result of nutmeg plantations. Nutmeg is one of the main commodities of the people of Banda Neira. Even the special Pala from Banda carries a long history for the Banda people.